In the shadow of the Moon [videorecording (DVD)] - Sington, David; Aldrin, Buzz; Bean, Alan, 1932-2018; Cernan, Eugene; Collins, Michael, 1930-2021-; Lovell, Jim; Mitchell, Edgar D.; Schmitt, Harrison H.; Scott, David Randolph, 1932-; Young, John, 1930-2018; Duke, Charlie, 1935- (Thinkfilm, 2008)
Between 1968 and 1972, the world watched in awe each time an American spacecraft voyaged to the Moon. Only 12 American men have walked upon its surface and they remain the only human beings to have stood on another world. Now for the first time, a combination of archival material from the original NASA film footage, much of it never before seen and interviews with the surviving astronauts tells the story of the Apollo space program.